Markets, Firms, and the Process of Economic Development - Moran, Peter; Ghoshal, Sumantra (Academy of Management Review, 1999)
We develop a framework to describe value creation as a process comprising resource combinations and exchanges and use the framework to show how organizations in general, and business firms in particular, interact with markets to create economic value for themselves, for their members, and for society. The theory offers an explanation of why neither a market nor a firm, by itself, can achieve adaptive efficiency and why institutional pluralism contributes to the process of economic development.